The action of the absolute idea: On the relationship between thought and reality in Hegels philosophy - Illetterati, Luca (Revista Eletrônica Estudos Hegelianos, 2024)
The action in which the absolute idea is realised is the conceptual node that, in Hegel's systematic horizon, brings into play the relationship between logic – as the science of pure thought – and (natural and spiritual) reality – considered as a dimension characterised, albeit in different forms and degrees, by a sphere of exteriority vis-à-vis the purity of thought.  In this sense, the action in which the absolute idea is realised is a place that is as decisive as problematic, because it is a matter of the problem that runs through the whole of modern philosophy and reaches its climax with Kant's transcendental philosophy, namely the forms of the relationship between mind and world, between epistemology and ontology, between thinking and being. The peculiarity of this action, meant as the locus of the questioning of the separation between thought and reality typical of modern thought, is the focus of this contribution. In the action that separates and unites logic from real philosophy, it is a matter both of deconstructing a dualistic view that sees thinking on the one side and reality on the other, with all the problems associated with the forms of relationship between two spheres assumed to be heterogeneous, and of the possibility of giving an account of the intelligibility of the world, that is, of giving an account of the power of thinking to manifest the reality of the world.
Keywords: logic; idea; externality; nature; spirit; action